2010
DOI: 10.1086/656579
|View full text |Cite
|
Sign up to set email alerts
|

Community‐Acquired Bacteremic Pneumococcal Pneumonia in Children: Diagnosis and Serotyping by Real‐Time Polymerase Chain Reaction Using Blood Samples

Abstract: RT-PCR allows diagnosis and serotyping of pneumococcal bacteremic community-acquired pneumonia in children and is an important tool for evaluating serotype distribution in culture-negative samples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
106
3
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 123 publications
(124 citation statements)
references
References 42 publications
13
106
3
2
Order By: Relevance
“…In total, 10% of children admitted to these hospitals were found to have community acquired bacteremic pneumococcal pneumonia by real-time PCR. 21 The results are comparable with our results when taking into consideration that Resti and others 21 studied a selected group of patients more likely to be infected with S. pneumoniae. Our study confirmed the importance of S. pneumoniae as a pediatric pathogen in Africa and supports the role of pneumococcal-conjugated vaccination as part of routine vaccines for Africa.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In total, 10% of children admitted to these hospitals were found to have community acquired bacteremic pneumococcal pneumonia by real-time PCR. 21 The results are comparable with our results when taking into consideration that Resti and others 21 studied a selected group of patients more likely to be infected with S. pneumoniae. Our study confirmed the importance of S. pneumoniae as a pediatric pathogen in Africa and supports the role of pneumococcal-conjugated vaccination as part of routine vaccines for Africa.…”
Section: Discussionsupporting
confidence: 90%
“…19,20 The higher RT-PCR method sensitivity compared with blood culture may explain these differences. The work by Resti and others 21 compared the performance of blood cultures and real-time PCR for the detection of S. pneumoniae bacteremia among children admitted with pneumonia to 83 Italian hospitals. Real-time PCR was 30 times more likely to detect S. pneumoniae bacteremia than blood cultures.…”
Section: Discussionmentioning
confidence: 99%
“…It has been observed that the increase in invasive disease owing to pneumococcal serotypes not included in PCV7 has been temporally associated with an increase in culture-negative empyema [19]. Where there has been extensive use of the polymerase chain reaction to detect pneumococcal DNA in empyema specimens, the role of these non-vaccine types as the leading cause of culture-negative empyema has been clearly established [20,21].…”
Section: The Clinical Spectrum and Burden Of Pneumococcal Diseasementioning
confidence: 99%
“…In a recent US study, the most common serotypes associated with empyema was serotype 3 (26.5 %) and 19A (22.4 %), followed by serotypes 7F (14.3 %) and 1 (12.2 %) [76]. Non-PCV7 serotype 1 has been linked to pediatric empyema cases [77,78]. Genotypic analysis using multi-locus sequence typing of pneumococcal serotype 1 isolates have shown that ST 306, a newly detected genotype, emerged after PCV7 implementation whereas STs-227, -228, and -304 were previously existing genotypes [78,79] .…”
Section: Pneumoniamentioning
confidence: 99%